Linear stability and resonance of triangular equilibrium points in elliptic restricted three body problem with radiating primary and triaxial secondary - Usha, T.; Narayan, A. (International Journal of Advanced Astronomy, 2016)
The present paper studies the linear stability of the triangular equilibrium points of the system. The system comprises of a radiating primary and a triaxial secondary in elliptic restricted three body problem. The existence of third order resonances has been shown and the linear stability has been analyzed for these resonance cases. For the resonance case, and , the conditions of the linear stability are satisfied and the system is stable. But, for the resonance cases and the system is unstable.